Cranial osteomyelitis associated with Pasteurella canis in broiler chickens - Cádiz, Leandro; Navarrete, Fernando; Torres, Paulina; Hidalgo, Héctor (Austral Journal of Veterinary Sciences, 2024)
Species of the Pasteurella genus are part of the oropharyngeal microbiota of many animal species. In poultry, Pasteurella multocida causes fowl cholera, the chronic manifestation of which can include neurological symptoms. Pasteurella canis causes osteomyelitis and other infections in humans. To the best of our knowledge, this is the first report of cranial osteomyelitis associated with Pasteurella canis in broiler chickens in Chile.